Medieval features and finds from Balfarg/Balbirnie, Fife - Russell-White, Christopher J; Ford, Barbara A; Graham, Catriona M M; Hall, Derek W; Holmes, Nicholas McQ; Stevenson, Sylvia (Proceedings of the Society of Antiquaries of Scotland, 1996)
Reports shallow pits and a possible mill-lade found whilst excavating an earlier site. There are details of: `The pottery' by Derek W Hall (1011–13); `Metal, glass, coins and jet' by Barbara A Ford (1014–15); `Coins' by Nicholas McQ Holmes (1015–16); and `Documentary sources' by Catriona M M Graham (1016).